(untitled) (INTERNATIONAL JOURNAL OF INDUSTRIAL AND PRODUCTION ENGINEERING, 2025)
The integration of nanomaterials in manufacturing processes has revolutionized modern industries by enhancing material properties, improving product performance, and increasing production efficiency. This paper explores the diverse applications of nanomaterials such as carbon nanotubes, graphene, and nanoceramics in sectors like aerospace, automotive, electronics, and biomedical engineering. These materials offer superior mechanical strength, thermal stability, and electrical conductivity, enabling the development of high-performance composites, wear-resistant coatings, and lightweight structures. Despite these advantages, challenges such as high production costs, safety concerns, and regulatory constraints hinder widespread adoption. Addressing these barriers requires advancements in cost-effective synthesis methods, recycling strategies, and regulatory frameworks. Additionally, the integration of nanomaterials with artificial intelligence and smart manufacturing technologies presents new opportunities for innovation. This study highlights recent developments in nanomaterial applications, their impact on industrial efficiency, and the future prospects of nanotechnology in sustainable and intelligent manufacturing. Continued research and interdisciplinary collaboration are essential to fully realize the transformative potential of nanomaterials in the manufacturing industry.